Assessing the in vivo data on low/no-calorie sweeteners and the gut microbiota. (February 2019) - Lobach, Alexandra R.; Roberts, Ashley; Rowland, Ian R.
Abstract: Low/no-calorie sweeteners (LNCS) are continually under the spotlight in terms of their safety and benefits; in 2014 a study was published linking LNCS to an enhanced risk of glucose intolerance through modulation of the gut microbiota. In response, an in-depth review of the literature was undertaken to evaluate the major contributors to potential changes in the gut microbiota and their corresponding sequelae, and to determine if consuming LNCS ( e.g., acesulfame K, aspartame, cyclamate, neotame, saccharin, sucralose, steviol glycosides) contributes to changes in the microbiome based on the data reported in human and animal studies. A few rodent studies with saccharin have reported changes in the gut microbiome, but primarily at high doses that bear no relevance to human consumption. This and other studies suggesting an effect of LNCS on the gut microbiota were found to show no evidence of an actual adverse effect on human health. The sum of the data provides clear evidence that changes in the diet unrelated to LNCS consumption are likely the major determinants of change in gut microbiota numbers and phyla, confirming the viewpoint supported by all the major international food safety and health regulatory authorities that LNCS are safe at currently approved levels. Highlights: Composition of the human gut microbiota is influenced by many dietary factors. Literature review identified in vivo studies on sweeteners and gut microbiota. Impact on microbiota confounded by uncontrolled background diet. Sweetener exposures typically exceeded ADI; therefore, human relevance limited. Current studies show no evidence of adverse effects of sweeteners on gut microbiota.